UMP appreciates services of frontliners as Aidilfitri approaches - Nor Salwana, Mohammad Idris (2022)
PEKAN, 23 April 2022 – Universiti Malaysia Pahang (UMP) appreciates the services and contributions of university frontliners who will continue to serve when most other staff will be on leave for the Eid celebration soon.